Business Combinations: Planning and Action. - Sterling, Robert R.; Healy, Robert E. (The Accounting Review, 1970)
Reviews the book "Business Combinations: Planning and Action," 1st ed., by Arthur R. Wyatt and Donald E. Kieso.